Diseño de un modelo de desarrollo turístico para la parroquia de río negro cantón Baños provincia de Tungurahua - Pazmiño Cahuasqui, Mónica Patricia (2014)
The subject of this project is to Design and develop a tourism model for Rio Negro parish, in Baños county in Tungurahua province, it's objective is to incentivate the community to promote and generate new incomes taking advantage high rates of visitors and natural resources. The first project is centered in soil conservation, increasing organic agriculture to produce an improved soil. The second project it's related to commercialization, which involves local population and give them the opportunity to participate in fares which can provide the national tourist the products. The third project is gastronomical and it's purpose is to generate a participation space for the citizens to select one dish, the most tasty, original and turn it into a typical Distinguish Parish dish.